Physical and Functional Properties of Roasted Tamarind (Tamarindus indica L.) Kernel Powder - Sudarmanto S. (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1996)
The objective of this experiment was to evaluate physical and functional properties of the roasted tamarind kernel powder (RTKP), compared to unroasted kernel powder (UTKP). Kernels were roasted at 150 - 160°C for 20 - 25 minutes, dehulled and ground to pass 48 mesh seive. Series of RTKP and UTKP were suspended in 80°C hot water, and their viscosities were measured at 30°C. Several TKP-sugar-water gels were prepared at pH = 3.0, and the gel strength was measured undi rectly by calculating the percentage of gel deformation. The results showed that there were no difference between the viscosities and gel strengths of RTKP and UTKP. Both RTKP and UTKP had good thickening power beginning from 1.5% (w/v) powder content. A strong TKP-sugar-water gel having defo rmation less than 15%, could be prepared using either RTKP or UTKP (1.75 - 2.5% w/w) and sugar (60%) at pH 3.